SENTIMEN ANALISIS MENGENAI UNHAN RI MELALUI MEDIA SOSIAL TWITTER - Lediwara, Nadiza; Denrineksa Bimorogo, Sembada; Khamas Heikmakhtiar, Aulia; Jaya Gainal, Ido; Naylil Karomah, Sufi; Fahmi, Khazali (Antivirus : Jurnal Ilmiah Teknik Informatika, 2024)
This study aims to determine public opinion regarding Universitas Pertahanan Republik Indonesia (UNHAN RI). As a new university, responses regarding public opinion need to be carried out so that the university can provide better services and educational programs. To see the public response to UNHAN RI, a Machine Learning method is used, namely Naïve Bayes. This Naïve Bayes modeling can help to classify public sentiment analysis towards UNHAN RI. By Naïve Bayes modeling, an accuracy value of 60.78% was obtained with three classification results, namely positive, negative, and neutral. The largest classification results were obtained in the positive class of 60.8%, the neutral class of 33.3%, and the negative class of 5.9%..